The Urgency of Clinical Legal Education through Developing of Legal Aid on Campus as an Effort to Realize a Humanist Law - Winarsih, Winarsih; Wulandari, Cahya (The Indonesian Journal of International Clinical Legal Education, 2019)
Legal education is an important things for law enforcement in Indonesia becauselaw enforcers were born from a legal education. Nowadays in the law enforcementthere are many problems, one of which is the law enforcement that do not providea justice because law enforcer only became the implementer of law. Theseconditions make a law could not fulfill the needs of society. Law tend to be rigidand interpreted as a regulations, whereas according to Satjipto Rahardjo stated thatthe law qualities are determined by the ability to serve the society. Lawenforcement nowadays are inseparable from the legal education, where thestudents are taught with a variety of legal theories, judicial practices in severalcourses and internship. However, this is not able to result the graduates who areable to put a law to serve the society. In addition, the students tend to be begin bythe difference between theories and legal realities. Basically, there are legal aid oncampus that can be used as a means to solve these problems, but the existence oflegal aid cannot be utilized properly. Therefore clinical legal education throughdeveloping of legal aid are needed to solve these various problems. This paperdiscusses two main issues: the first, how are the urgency of clinical legal educationthrough developing of legal aid on campus? The second, how are theimplementation of clinical legal education through developing of legal aid oncampus? The results of this paper are: the first clinical legal education throughdeveloping of legal aid on campus is important to make the students understandthe society problems. Additionally after graduation, the students are expectedbecoming law enforcer who provide justice. Furthermore the graduates of the legaleducation are expected to enforce the law progressively based on the value ofjustice. The second, clinical legal education are implemented through the studentwith given more time to practice in the society so that the students know thevarious problems in society and compare with the legal theories. Furthermoreparadigm of the lecturer is also need to be changed with directed to give practicalcourses so that the students know the case directly in the society. Optimizing theexistence of legal aid on campus also become important things because it can beused to the students to provide services toward the society on campus. These waysare expected to the students who are able to practice in the society and makehumanist law.